The maximum value of alfalfa meal in protein supplements for pigs on pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Since pastures for swine are often poor, inadequate, or unavailable in Kansas, there is a growing appreciation of the value of alfalfa hay or meal in the rations of all swine brood sows (and pigs being fed for market). This experiment was designed to secure information on the maximum use of alfalfa meal in protein supplemental mixtures as a substitute for pasture, tested with pigs on summer pasture and in dry lot.
Keywords: Swine; Alfalfa meal; Protein